Dental ceramics microstructure, properties and degradation - Bergmann, Carlos Pérez (Topics in mining, metallurgy and materials engineering)
This book gives an introduction to the mechanical behavior and degradation of dental ceramics and guides the reader through their performance under effect of oral environments. It addresses the different kinds of dental ceramics, their properties, degradation and mechanical aspects with less emphasys on the physics and chemistry involved, which makes the reading interesting for beginners in the field. In each chapter, the reader will learn about the mechanical behavior of dental ceramics and each phenomenon involved in their application, besides finding some practical examples of their use in dental clinics, their manufacturing procedures and types of degradation. The clear language and the application-oriented perspective of the book makes it suitable for both professionals and students who want to learn about dental ceramics.